Subjective well-being pada emerging adulthood: Bagaimana peran Problem Focused Coping? (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2022)
Abstract Exploration of identity in individuals in the emerging adulthood period has affected subjective well-being which is characterized by the emergence of negative affect to the point where evaluations of low life satisfaction and problem-focused coping are shown to be one of the factors that influence subjective well-being. This study aims to determine the relationship between problem focused coping and subjective well-being in emerging adulthood. Sampling in this study using non-probability sampling technique by accidental sampling. This study involved 112 people in Indonesia who were in the emerging adulthood period, namely 18-25 years of age. This type of research is quantitative research using data analysis techniques, namely the Pearson Product Moment correlation test and showing the results of the value of rxy = 0.721 with a significance of 0.000 (p <0.01). This means that there is a very significant positive relationship between problem focused coping and subjective well-being in emerging adulthood. Thus, the higher the individual's problem focused coping in the emerging adulthood period, the higher the subjective well-being in emerging adulthood, and vice versa. Abstrak Eksplorasi identitas pada individu periode emerging adulthood telah mempengaruhi subjective well-being yang ditandai dengan timbulnya afek negatif hingga menunjukkan evaluasi kepuasan hidup yang rendah dan problem focused coping menjadi salah satu faktor yang mempengaruhi subjective well-being. Penelitian ini bertujuan untuk mengetahui hubungan antara problem focused coping dengan subjective well-being pada emerging adulthood. Pengambilan sampel pada penelitian ini menggunakan teknik non probability sampling secara accidental sampling. Penelitian ini melibatkan sebanyak 112 masyarakat di Indonesia yang berada pada periode emerging adulthood yaitu usia 18-25 tahun. Jenis penelitian ini yaitu penelitian kuantitatif dengan menggunakan teknik analisis data yaitu uji korelasi Pearson Product Moment dan menunjukkan hasil nilai rxy = 0,721 dengan signifikansi 0,000 (p < 0,01). Artinya, terdapat hubungan positif yang sangat signifikan antara problem focused coping dengan subjective well-being pada emerging adulthood. Sehingga, semakin tinggi problem focused coping individu periode emerging adulthood maka semakin tinggi subjective well-being pada emerging adulthood, begitupun sebaliknya.